(untitled) (Journal of Engineering, 2014)
A Longitudinal opening is used to construct hollow core beam is a cast in site or precast or pre stressed concrete member with continuous voids provided to reduce weight, cost and, as a side benefit, to use for concealed electrical or mechanical runs. Primarily is used as floor beams or roof deck systems. This study investigate the behavior of six beams (solid or with opening) of dimension (length 1000 x height 180 x width120mm) simply support under partial uniformly distributed load, four of these beam contain long opening of varied section (40x40mm) or (80x40mm). The effect of vertical steel reinforcing, opening size and orientations are investigated to evaluate the response of beams. The experimental behavior based on load-deflection measured at central and quarter of tension zones. The experimental test result shows the presence of Hollow decrease the load carrying capacity by about (37.14% to 58.33%) and increased the deflections by about (71.6% for (Hollow ratio 7.4%) to 75.5% for (Hollow ratio 14.8%)) for same applied load compared with solid beams with the same properties. The increase shear steel reinforcing will decrease all the deformations at all stages of loading, but particularly after initial cracking and give enhancement in ultimate load capacity of beams by about 31.5% with increasing the amount of shear steel reinforcing by about 50%. Finally, ductility is increased in all cases under partial uniformly distributed load when hollow ratio decreased by about 50% or increased in shear steel reinforcing by about 50%